Gospodarski subjekti na trgu in evropske dimenzije 2018 - Rijavec, Vesna (2019)
Corporate Entities at the Market and European Dimensions 2018. The book with the title Corporate Entities at the Market and European Dimensions 2018 is a scientific monograph by several authors of individual chapters. The authors analyzed the legal positions in relation to smart contracts, controlled company and legal protection of shareholders and creditors, the effect of spatial planning and construction legislation into property law, media law and data protection under the General Data Protection Regulation (GDPR) etc. The book contains contributions from the field of public and private law. Individual authors clearly express their views, the difference between the summaries and their own views is clear. The authors are discussing with the power of the arguments with the views in legal theory and jurisprudence, which increases the practical value of the monograph. The book represents a contribution to the development of legal science.
Keywords: scientific monographs; Slovenia; European commercial law; enforcement law; insolvency law; labor law; tax law; commercial contract law; company law